Tipos de forrajeo y gremios alimenticios de la avifauna en dos bosques sobre arena blanca de la Reserva Nacional Allpahuayo Mishana, Loreto - Perú - Alva Ocampo, Betsy (2016)
From October 2014 to March 2015 and with the objective of knowing the types of foraging and food guild of the bird in two white sand forests of the Allpahuayo Mishana National Reserve (RNAM), two plots of one hectare were evaluated (“Varillal high wet” -VAH-, for its acronym in Spanish - and “Varillal high dry” –VAS, for its acronym in Spanish-), using the method of Counting Point of brid (CPB). A total of 10 types of foraging were observed: going out, reaching, chopping, hanging, hovering, picking up, throwing, spying, reaching with jump and searching on the branch; In 76 species of birds found among the white sand forest, the most dominant was going out, followed by reaching and the least dominant was spying. Six insectivorous, frugivorous, frugivorous / insectivorous, frugivorous / granivorous, nectarivorous and carnivorous food guilds were recorded, the most dominant was insectivorous followed by frugivorous and the least dominant were nectarivorous and carnivorous.